Oral Contraceptives after Myomectomy: A Short Term Trial - Stefano Luisi; Valentina Ciani; Massimo Gabbanini; Sofia Sollazzi; Michela Torricelli; Francesco Calonaci; Felice Petraglia (International Journal of Endocrinology)
Following myomectomy the rate of fertility is restored and pregnancy may be attempted with a good outcome. In the present study a 3 month treatment with OCs in a group of women after a myomectomy was evaluated. The drug compliance and side effects, the benefits of OC in order to reduce symptoms, to increase post-surgical hemoglobin levels and to avoid an early pregnancy after myomectomy were analyzed. A group of women (𝑛=55) each with myoma ≥5 cm was recruited: they presented menorrhagia, pelvic pain, dyspareunia and dysmenorrhae. After laparotomic myomectomy the women were divided into 3 groups. Group 1: women (𝑛=16) treated with pill A (15 mcg of ethynilestradiol + 60 mcg of gestodene); group 2: women (𝑛=23) treated with pill B (20 mcg of ethynilestradiol + 100 mcg of levonorgestrel); group 3: women (𝑛=16) treated with a placebo (oral calcium). After three months from myomectomy and treatment patients in each group reported a reduced menorrhagia, dismenorrhea and pelvic pain. Serum haemoglobin levels increased in all women (𝑃<.05). No pregnancy occurred in any group and the compliance was good. A post surgery treatment by using oral contraceptives guarentees pregnancy prevention, associated with reduction of pain, and improvement of haematologic conditions.